PENDAMPINGAN PEMBUATAN SALURAN TERSIER OLEH P3A (PERKUMPULAN PETANI PEMAKAI AIR) PADE PACU DI DESA JEROWARU, KABUPATEN LOMBOK TIMUR: Assistance in the Construction of a Tertiary Channel by the P3A (Water Users Association) in Pade Pacu in Jerowaru Village, East Lombok Regency - Yamin, Muhamad; Dharma S., Bagus Widhi; Winardi, Agus; Isnasari, Wiriyanti; Isnaeni, Isnaeni; Rahman, Rahman; Ulfa, Syarifatul; Aminullah, Aminullah (Al-Amal: Jurnal Pengabdian Masyarakat, 2025)
This community service activity was carried out in Pade Pacu Village, Jerowaru District, East Lombok Regency, which has productive agricultural land but faces challenges in irrigation water distribution. The objective of this activity was to assist the Pade Pacu Water Users Farmers Association (P3A) in constructing a tertiary canal to improve the efficiency of water distribution to agricultural land. Implementation methods included site surveys, technical planning, canal construction, and management assistance. The results showed that the tertiary canal, 300 meters long and 0.4 meters wide at the base and 0.5 meters wide at the top, was able to improve water distribution to 20 hectares of rice fields. This activity also increased the participation and technical skills of Pade Pacu P3A members in managing the irrigation network.